PENGARUH TRUST, RISK AND TECHNOLOGY ACCEPTANCE MODELS TERHADAP KEPUTUSAN NASABAH DENGAN MINAT NASABAH SEBAGAI VARIABEL INTERVENING - Ismulyaty, Sri; Siswantini, Wiwin (JURNAL EKOMBIS REVIEW, 2017)
Sri Ismulyaty dan Wiwin Siswantini: The purpose of this study was to determine the influence of trust, risk and technology acceptance models, perceived case of use, perceived usefulness, perceived of credibility, the customers' interest in using internet banking? And how to influence customers' interest in using internet banking to the decision in dealing with internet banking? As well as how to influence customers' interest in using internet banking mediates the relationship between trust, risk and technology acceptance models with decisions in dealing with internet banking?Discussion of the results of this study can be drawn the following conclusions: Trust affect the customers' interest in using internet banking, Risk affect the customers' interest in using internet banking, Perceived case of use affect the customers' interest in using internet banking, Perceived usefullnes affect the interest of the customer in using internet banking, Perceived of credibility affect the customers' interest in using internet banking, interest customers in using internet banking influence the decision in the transaction, interest customers in using internet banking may mediate the relationship between trust, risk and technology acceptance models with the decision in the transaction with internet banking.Key Words: Trust, Risk And Technology Acceptance Model Keputusan Nasabah, Minat Nasabah